Insomnia in migraine patients: impact on disability, depression, and anxiety - a partial analysis - Sakamoto, Karina Hikari; Campos, Gabriela Rosa; Frederico, Regina Célia Poli; Oliveira, Carlos Eduardo Coral de; Reiche, Edna Maria Vissoci; Bello, Valéria Aparecida; Silva, Aline Vitali da (Headache Medicine, 2024)
Introduction: Migraine is a complex neurological disorder with profound interactions with the body's homeostasis, particularly the sleep-wake cycle.Objective: To evaluate the effect of sleep parameters on individuals with migraine and their association with migraine severity and mood.Methods: This is a cross-sectional study involving 49 participants diagnosed with migraine and treated at the Headache Clinic of PUC-PR, Londrina-PR, Brazil. Demographic, anthropometric, and clinical data were collected, along with responses to validated questionnaires: Migraine Disability Assessment (MIDAS), Headache Impact Test (HIT-6), 12-item Allodynia Symptom Checklist (ASC-12), General Anxiety Disorder-7 (GAD-7), Beck Depression Inventory (BDI), Insomnia Severity Index (ISI), Epworth Sleepiness Scale (ESE), and Morningness-Eveningness Questionnaire (MEQ). Spearman's correlation was used to examine the relationships between variables, considering statistical significance for p